Using appreciative inquiry as a framework to enhance the patient experience - Kerry Moorer; Schawan Kunupakaphun; Elilzabeth Delgado; Matthew Moody; Christina Wolf; Karen Moore; Pracha Eamranond (The Beryl Institute, 2017)
The following case depicts the journey of a non-profit hospital in an under-served community and its attempts to turn around suffering patient experience. The Hospital turned to the theories of Appreciative Inquiry and the power of a strengths-based approach to create a framework to support the patient experience initiatives. Hospital leadership led the formation of a Patient Experience Team to implement ten initiatives in order increase the top box score in the domain of willingness to recommend the hospital, as that was selected as a global measure of success for the overall improvement project.